Sodium selenite antagonizes trimethyl tin-induced chicken hepatotoxic hepatitis through the RNS/NF-κB/NLRP3 pathway - Xinzhang Chen; Xu Lin (Poultry Science)
Trimethyl tin (TMT) is a good stabilizer for plastic products but is also a toxic environmental pollutant. Selenium has good antioxidant and anti-inflammatory properties and has been widely used in the poultry industry. However, it has not been reported whether selenium enrichment can antagonize TMT-induced viral hepatitis in poultry. To fill this gap, AA broiler models exposed to TMT for 42 d were established and fed a Se-enriched diet at the same time. H&E staining showed that selenium could significantly alleviate TMT-induced liver inflammation. Further analysis of the underlying mechanism revealed that TMT induced nitrosation stress (RNS), increased NO content and iNOS expression, which in turn activated the NF-κB/NLRP3 pathway and induced pyroptosis. However, selenium enrichment can reverse this situation, that is, reduce the occurrence of RNS, reduce the degree of pyroptosis, and thus alleviate the occurrence of inflammation. In our study, we demonstrated for the first time that TMT could induce hepatotoxicity other than neurotoxicity in poultry and that selenium could antagonize TMT-induced hepatotoxic hepatitis in chickens through the RNS/NF-κB/NLRP3 pathway.